KONTROVERSI HUKUM PEGADAIAN SYARIAH - Delima Sari Lubis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
Pawn is a covenant debts, where people are owed will pawn the goods as collateral for the debt. In general, scholars have agreed that the pawn is permissible. The existence of syariah pawn has juridical implications on the economic development of sharia in Indonesia. Thus, the prospect of sharia pawnshops forward very unusual, because the response of the people are very nice. But in practice sharia pawnshops are some things that are still disputed by several parties, among others; First, sharia pawning not completely remove the system of interest, but rather change the flowers to save costs on the basis of Ijarah contract (service fee). secondly , the rules on product qardh Bank Indonesia backed gold, it is feared will be a trigger speculation practices. Both of these things would be avoided if there is a good cooperation of the various parties involved, both the mortgage, practitioners, economists Islam , businesses and government. So the practice of sharia pawnshops really in accordance with the rules of Islam